Impact of obstetric learning strategy on creative thinking and some basic volleyball skills Aircraft for students of the Faculty of Physical Education and Sports Sciences (Journal of Namibian Studies : History Politics Culture, 2023)
The study is important in its use of an obstetric learning strategy to recognize its impact on creative thinking. The transmission skills are discussed below, where we prepare and receive the transmission by volleyball. The researchers used the experimental curriculum in the manner of the two equal groups to apply the study procedures. The research sample was 40 second-stage students of the Faculty of Physical Education and Sports Sciences - Qadisiyah University. They were randomly divided into a police group, the "E" division was 20 students as a Pilot group and division (d) was 20 students. Necessary tools and devices have been used which included the strategy of obstetric learning and exploratory experience. The main field of experience involved post testing and the application of the strategy and then remote testing. The researchers concluded the student's need this strategy to help them improve creative thinking in learning the skills of preparation, reception and dispatch from below fending off volleyball. They recommend utilizing and giving sufficient space to the education units' obstetric learning strategy because of its active role in creative thinking and learning skills.